The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.5222/iksst.2018.82787
|View full text |Cite
|
Sign up to set email alerts
|

Patient Blood Management

Abstract: ÖZHasta Kanı Yönetimi (HKY), gereksiz transfüzyonları önlemek yanında hastanın transfüzyon alma olasılığını en aza indirmeye ve kendi kan rezervini optimize etmeye yönelik tüm uygulamaları içeren bir kavramdır. En çok elektif cerrahiye hazırlanan hastalarda uygulanmakta olup transfüzyon miktarında önemli oranda azalma, maddi olarak tasarruf ve hasta açısından daha iyi tıbbi sonuçlar sağladığı gösterilmiştir. Bu makalede, Dünya Sağlık Örgütü'nün de sağlık uygulamalarının ayrılmaz bir parçası olması gerektiğini … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…According to World Health Organization (WHO), cardiac insufficiency is defined as a syndrome emerged as a result of the filling the ventricles with blood and/or the breakdown of their blood pumping property due to the structural and/or functional failure of the heart (1,2). It is reported that there are 5 million cardiac insufficiency patients and it is added 550.000 new cardiac insufficiency cases per year in United States of America (USA) (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…According to World Health Organization (WHO), cardiac insufficiency is defined as a syndrome emerged as a result of the filling the ventricles with blood and/or the breakdown of their blood pumping property due to the structural and/or functional failure of the heart (1,2). It is reported that there are 5 million cardiac insufficiency patients and it is added 550.000 new cardiac insufficiency cases per year in United States of America (USA) (3,4).…”
Section: Introductionmentioning
confidence: 99%